Atrial Fibrillation and the Weekend Effect Regarding Cardioversion, Length of Stay, Readmission, and Mortality. Issue 3 (September 2018) - Zaremski, Lynn; Mazori, Alon; Shulman, Eric; Kargoli, Faraj; Shah, Tina; Chudow, Jay Julius; Leiderman, Ephraim; Di Biase, Luigi; Fisher, John; Ferrick, Kevin; Krumerman, Andrew
Abstract : Background: The weekend effect is a phenomenon in which worse outcomes have been found to occur over the weekend. This has been investigated in the context of stroke, ST-elevation myocardial infarction, and pulmonary embolism among others. Atrial fibrillation (AF) is the most common sustained arrhythmia, and admissions for AF have been increasing. However, few studies exist investigating the existence of a weekend effect regarding AF. Previous studies have been limited by a pragmatic but unrealistic definition of the weekend starting at midnight on Friday and ending midnight on Sunday. In addition, the studies that exist have conflicting data regarding outcomes of mortality and length of stay (LOS). Methods: Over a 5-year period, 3233 patients with a primary diagnosis of AF were admitted to an academic center. A retrospective analysis was performed to determine rates of cardioversion, 30-day readmission, 30-day mortality, LOS, and time to cardioversion among patients admitted over the weekend compared with those admitted during the work week. Weekend was defined as the 48-hour period, including Saturday and Sunday. Results: Baseline demographics and common risk factors were found to be equivalent in weekend admissions compared with weekday admissions. These characteristics were found to be equivalent in those who underwent cardioversion and those who did not. There was no statistically significant difference between groups in odds of cardioversion, 30-day readmission, or 30-day mortality. Difference in mean LOS and mean time to cardioversion was not statistically significant between groups. Conclusion: In conclusion, a weekend effect was not identified regarding AF in an academic hospital.